THE IMPACT OF SERVICE QUALITY ON MUSLIM CUSTOMERS IN SHARIAH COMPLIANT HOTEL - Albattat, Ahmad; Ahmad Pitra, Jumli; Nishalini A/P Mahendran; Azila Azmi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Shariah compliant hotel is a new innovative and creative services found in the hotel industry. This development can be found in countries where Muslim residents are the majority population as Malaysia and Indonesia. This research aims to study the impact of service quality and Muslim customers, to study the relationship between facilities and Muslim customers, to study the relationship between food and beverage department and Muslim customers, and to study the relationship between Muslim customers and the Shariah compliant hotel. The data collected using questionnaires distributed to 110 guests in halal hotel and SPSS20 was used to analyze the data. The findings showed that Muslim Customers had a positive influence on the Shariah compliant hotel. The Shariah-compliant hotels are not only limited to serving halal food and drink, but the operation throughout the hotel would also be managed based on Shariah principles such as the Quran and prayer mats available in each room, no alcohol, Beds and toilet positioned so as not to face the direction of Mecca, Bidets in the bathrooms, Prayer rooms and Islamic funding